Relationship of Lifestyle and Health Status with the Event of Anemia in Adolescent - Misroh Mulianingsih; Sopian Halid; Irwan Hadi (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
The highest incidence of anemia was found in adolescent girls (10-19 years) compared to adolescent boys. This is because young women experience menstruation every month and some of them go on a diet so that there is a lack of iron in the blood which is useful for the formation of Hb, causing anemia. The purpose of this study was to determine the relationship between lifestyle and health status with the incidence of anemia in adolescent girls at SMAN 9 Mataram. The design of this research is analytic observational with a cross sectional research design and the number of samples is 63 students with purposive sampling technique. Primary data were obtained through a questionnaire consisting of 33 questions (5 items for physical activity, 5 questions for modern medicine consumption, 7 questions for traditional medicine consumption and 6 questions for infectious diseases). The questionnaire has been tested for validity with a value (rcount > rtable) and the reliability test results for each variable have a value greater than 0.600 so that all research instruments can be declared reliable and can be used for further analysis. Secondary data was obtained from anemia screening data at the Selaparang Health Center. Data were analyzed univariately and bivariately with Chi-Square using =0.05. The results showed that there was a relationship between consumption of modern medicine (p = 0.040; OR = 0.862), consumption of traditional medicine (p = 0.042; OR = 1.070), and nutritional status of BMI/U (p = 0.043) with the incidence of anemia in adolescent girls. Meanwhile, there was no correlation between physical activity (p=0,288; OR=1,108), breakfast (p=0,238; OR=0,354), and infectious diseases (p=0,145; OR=2,047) with the incidence of anemia in adolescent girls.